(3QO QSGdI CfehPL GdYdhes - (3GdMSjfj, GdOTJcj, GdTjQGRj, ZjGK GdOjf, efUhQ Hf eMeO Hf EHQGgje, J (B948(3g`s
(3ChdgG (B:s
(3Gddge GfUQfG Ydi Gdbhe GdcGaQjf(B... (3hHYO (B... (3gPg deYGJ cGTaI Yf XdeGJ(B...s
(3BNQgG (B:s
(3hefgG Cf jchf aj GdcdGe JThjT hJMQja hcCfg jbhd(B... (3JeJ GdMGTjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B304s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B918s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs